Exploring recent trends in Northern Hemisphere blocking - Barnes, E; Dunn-Sigouin, E; Masato, G; Woollings, T (American Geophysical Union, 2014)
Observed blocking trends are diagnosed to test the hypothesis that recent Arctic warming and sea ice loss has increased the likelihood of blocking over the Northern Hemisphere. To ensure robust results, we diagnose blocking using three unique blocking identification methods from the literature, each applied to four different reanalyses. No clear hemispheric increase in blocking is found for any blocking index, and while seasonal increases and decreases are found for specific isolated regions and time periods, there is no instance where all three methods agree on a robust trend. Blocking is shown to exhibit large interannual and decadal variability, highlighting the difficulty in separating any potentially forced response from natural variability. ©2014. American Geophysical Union. All Rights Reserved.